Synthesis and evaluation of novel pyrazole-imidazole hybrids as antimicrobial candidates. Issue 18 (17th September 2021) - Punia, Suman; Verma, Vikas; Kumar, Devinder; Kumar, Ashwani; Deswal, Laxmi; Parshad, Mahavir
Abstract: The present study describes a facile and efficient synthesis of 1-( N -arylacetamide)-4-phenyl-2-pyrazolyl-imidazole 7a–7t by reacting 1-(4-phenyl-1 H -imidazol-2-yl)-1 H -pyrazole (3a )/3, 5-dimethyl-1-(4-phenyl-1 H -imidazol-2-yl)-1 H -pyrazole (3b ) with 2-bromo- N- substitutedacetamide 6a–6j ) in good yield. The structure of compounds 7a–7t are confirmed by various spectral techniques. All the prepared compounds are examined for in-vitro antimicrobial activities against three bacterial strains; S. aureus, B. subtilis and E. coli and two fungal strains; C. albicans and A. niger . The synthesized analogues show moderate inhibitory activity against tested bacterial strains and the compounds 7a, 7b, 7l, 7m and 7r exhibited good activity against C. albicans. Most of the compounds obey the Lipinski rule of five. The compound 7b is docked in the active site of C. albicans sterol-14α-demethylase and DNA gyrase to find the binding conformation. Graphical Abstract: UF0001